Microvascular biodistribution of L19-SIP in angiogenesis targeting strategies - Czabanka, Marcus Alexander; Parmaksiz, Güliz; Bayerl, Simon H.; Nieminen, Melina; Trachsel, Eveline; Menssen, Hans D.; Erber, Ralf; Neri, Dario; Vajkoczy, Peter (European journal of cancer, 2011)
Introduction - Various strategies using L19-mediated fibronectin targeting have become useful clinical tools in anti-tumour therapy and diagnostics. The aim of our study was to characterise the microvascular biodistribution and binding process during tumour angiogenesis and after anti-angiogenic therapy. - Materials and methods - SF126 glioma and F9 teratocarcinoma cells were implanted into dorsal skin fold chambers (SF126: n=4; F9: n=6). Using fluorescence and confocal intravital microscopy the biodistribution process was assessed at t=0h, t=4h and t=24h after intravenous application of Cy3-L19-SIP. Sunitinib treatment was applied for six days and microscopy was performed 2 and 6days after treatment initiation. Analysed parameters included: vascular and interstitial binding, preferential binding sites of L19-SIP, microvascular blood flow rate, microvascular permeability. Histological analysis included CD31 and DAPI. - Results - L19-SIP showed a specific and time-dependent neovascular binding with a secondary extravasation process reaching optimal vascular/interstitial binding ratio 4hours after iv administration (F9: L19-SIP: vascular binding: 74.6±14.5; interstitial binding: 46.8±12.1; control vascular: 22,2±16.6). Angiogenic sprouts were preferred binding sites (F9: L19-SIP: 188±15.5; RTV: 90.6±13.5). Anti-angiogenic therapy increased microvascular hemodynamics (SF126: Su: 106.6±13.3μl/sec; Untreated: 19.7±9.1μl/sec) and induced increased L19-SIP accumulation (SF 126: t24; Su: 92.6±2.7; Untreated: 71.9±5.9) in therapy resistant tumour vessels. - Conclusion - L19-SIP shows a time and blood-flow dependent microvascular biodistribution process with angiogenic sprouts as preferential binding sites followed by secondary extravasation of the antibody. Microvascular biodistribution is enhanced in anti-angiogenic-therapy resistant tumour vessels.